Is macro prudential regulation possible? - Paul Wachtel (Budgetary Research Review (BRR), 2013)
The 20th century consensus regarding the role of a central bank - to maintain price stability was upset by the global financial crisis of 2007-2009. Central banks changed their mode of behavior and new regulatory structures were introduced around the world. In this essay, I examine one of the principle new approaches to regulation - regulating macro prudential risk. I explain what it means and assess the approaches that have been suggested.
Keywords: 330